Problem Tree Force Field analysis of injection of agonist opioid medications and benzodiazepines in North Macedonia - Ignjatova, LA (AU- CNS, 2022)
Background: The aim of this paper is to analyse the roots and effects of injection of agonist opioid medication (AOM) and benzodiazepines by many patients participating in an agonist opioid treatment (AOT) programme and the factors involved both for and against the proposed change for solving this problem. Methods: For this purpose, we used Problem Tree Force Field analysis. “Problem Tree” was used to identify the focal problem and the associated causes and effects with the aim of identifying solutions to the problem by mapping out the anatomy of these causes and their effects. By rephrasing each of the problems into desirable outcomes, root causes and consequences are turned into solutions. Goals for change were then set in the “Force Field Analysis” to identify the factors and subsequent pressures for and against the proposed change. Results: The analysis showed that the black market near the AOT service and the opportunity to sell take home therapy providing both financing and “borrowed therapy” with “interest”, aggravating poverty, unemployment, non-integration into the community, lack of social support, incoherent harm reduction interventions, exchange of injection equipment in front of the service, lack of education of out-reach workers and lack of staff are just some of the reasons for abuse and diversion of the AOM. This leads to a poor treatment outcome with the resulting consequences for patient health, staff, and the environment and which contributes to violence and stigma making recovery unlikely. Drivers and resistors are also analysed, which help in visualizing the possibilities for achieving the proposed change and to determine which decisions and actions are needed and available. Conclusions: This tool shows the reality and helps to find solutions. New formulations of AOM can be one of the solutions to the diversion and abuse of AOM.
Keywords: Abuse; Diversion; New Formulation of AOM